A simple method for indexing powder diffraction patterns of cubic materials:(1) using the θ-values of reference - Kamwaya, ME (Tanzania Journal of Science, 2021)
From the values of sin2θ taken from powder photographs of the cubic crystal system, a variable constant, K, which is a multiple of (h2 + k2 + l2) can be determined. The smallest value of sin2θ1 gives rise to a multiple of one, two, or three which corresponds to the smallest value of Σhl2 for the primitive, bcc and fcc crystals, respectively. The old assumption that when indexing, the occurrence of numbers of the form (h2 + k2 + l2) = 8n + 7, where n = 0.1.2.3… should cause each of (h2 + k2 + l2) to be multiplied first by two before indexing, is disapproved.